2003
DOI: 10.1046/j.1365-2567.2003.01634.x
|View full text |Cite
|
Sign up to set email alerts
|

A potent adjuvant effect of CD40 antibody attached to antigen

Abstract: SUMMARYThere is great potential for novel vaccines based on recombinant proteins and synthetic peptides. Unfortunately these antigens often lack the immunogenicity of whole, killed pathogens used in traditional vaccines. Thus there is strong interest in the identi®cation of immunological adjuvants with low reactogenicity, but high potency, to enhance immune responses and realize the potential of these new vaccine strategies. CD40 antibodies have been shown to have adjuvant effects when administered at very hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 32 publications
1
56
0
Order By: Relevance
“…However, in the present studies, the immunized mice showed no signs of distress, and spleen size and cell counts were not increased by the immunizations (data not shown). This contrasts with the splenomegaly, septic shock-like effects and occasional mortality observed when agonistic anti-CD40 antibodies were given systemically (8,94). The most revealing experiment, however, was functional and involved separating the pScGag antigen plasmid from the pSP-D-CD40L adjuvant plasmid.…”
Section: Construction Of Expression Plasmids For 1- 2- and 4-trimermentioning
confidence: 90%
See 1 more Smart Citation
“…However, in the present studies, the immunized mice showed no signs of distress, and spleen size and cell counts were not increased by the immunizations (data not shown). This contrasts with the splenomegaly, septic shock-like effects and occasional mortality observed when agonistic anti-CD40 antibodies were given systemically (8,94). The most revealing experiment, however, was functional and involved separating the pScGag antigen plasmid from the pSP-D-CD40L adjuvant plasmid.…”
Section: Construction Of Expression Plasmids For 1- 2- and 4-trimermentioning
confidence: 90%
“…Agonistic anti-CD40 antibodies also act as a general vaccine adjuvant (8) and synergize with Toll-like receptor agonists to elicit profound vaccine-induced CD8 ϩ T-cell responses (4). However, these antibodies induce splenomegaly and shock-like symptoms unless used in small amounts in a single administration (8,94), which raises concerns about using agonistic anti-CD40 antibodies in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used agonistic anti-CD40 antibodies to activate CD40-bearing cells to enhance CD8 T-cell responses (3,4) and antitumor responses (13)(14)(15). Agonistic anti-CD40 antibodies also act as a general vaccine adjuvant (16) and synergize with Toll-like receptor agonists to augment vaccine-induced CD8 T-cell responses (17). However, these antibodies induce splenomegaly and shock-like symptoms unless used in small amounts in a single administration (15,16), which raises concerns about using systemic agonistic anti-CD40 antibodies in humans.…”
mentioning
confidence: 99%
“…Agonistic anti-CD40 antibodies also act as a general vaccine adjuvant (16) and synergize with Toll-like receptor agonists to augment vaccine-induced CD8 T-cell responses (17). However, these antibodies induce splenomegaly and shock-like symptoms unless used in small amounts in a single administration (15,16), which raises concerns about using systemic agonistic anti-CD40 antibodies in humans. Modulated local expression of CD40L at relatively lower levels by DNA or replication-defective viral vaccines could provide a safe alternative to overly potent systemic stimulation by agonistic anti-CD40 Ab or high doses of CD40L protein.…”
mentioning
confidence: 99%
“…[21][22][23] Many CD40mAbs mimic the natural ligand, CD154. We showed previously that immunization of mice with low doses of anti-CD40mAb conjugated to Ag results in enhanced primary 24 and secondary Ab responses, increased IFN-␥ production, and enhanced delayed hypersensitivity responses, indicating an initiation of a Th1-like cell response. 25 It is widely known that Th1 immune responses are required for efficient tumor cell destruction; therefore, we considered the use of an anti-CD40mAb as an adjuvant might be beneficial in lymphoma Id vaccination.…”
Section: Introductionmentioning
confidence: 92%